2010
DOI: 10.3109/10253891003671690
|View full text |Cite
|
Sign up to set email alerts
|

Adverse life events, area socio-economic disadvantage, and adolescent psychopathology: The role of closeness to grandparents in moderating the effect of contextual stress

Abstract: The study, using data from 801 11-16-year-olds clustered in 68 schools across England and Wales, tested whether closeness to grandparents moderates the association between contextual stress and adolescent psychopathology and prosocial behavior, measured with the strengths and difficulties questionnaire (SDQ). Contextual stress was measured at both school area level (assessed with the index of multiple deprivation) and child level (assessed, as life stress, with the number of proximal and distal adverse life ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…The large variety in prevalence rates is likely to reflect differing ADHD measures and potentially geographic variation between studies; In a German sample, DSM-IV prevalence is reported [50]; in Colombia a DSM symptom questionnaire was used in conjunction with the Conners' scale [51], and Ornoy [52] utilised the Conners' questionnaire with a cut-off point of 21 and over in an Israeli sample. Using the Duncan Socioeconomic Index, one study found no significant difference of SES between children with and without ADHD [53], similarly one study did not find an association between Index of Multiple Deprivation (IMD) and hyperactivity [54], however two studies found an association between low SES and ADHD [55,56].…”
Section: Index Of Sesmentioning
confidence: 98%
“…The large variety in prevalence rates is likely to reflect differing ADHD measures and potentially geographic variation between studies; In a German sample, DSM-IV prevalence is reported [50]; in Colombia a DSM symptom questionnaire was used in conjunction with the Conners' scale [51], and Ornoy [52] utilised the Conners' questionnaire with a cut-off point of 21 and over in an Israeli sample. Using the Duncan Socioeconomic Index, one study found no significant difference of SES between children with and without ADHD [53], similarly one study did not find an association between Index of Multiple Deprivation (IMD) and hyperactivity [54], however two studies found an association between low SES and ADHD [55,56].…”
Section: Index Of Sesmentioning
confidence: 98%
“…Early adverse stress trauma environments are implicated in ADHD over national boundaries [122124]. Deprivation in social and environmental conditions may perturb early cellular patterns of neurodevelopment that are manifested as disorder expression in later life [125], with aspects of ADHD originating in early deprivation [126,127].…”
Section: Neurotransmittersmentioning
confidence: 99%
“…Both models had acceptable variance inflation factor and tolerance values (Field, 2009). In block 1, VIF ranged from 1.01 to 1.02 and tolerance ranged from .98 to .99.…”
Section: Resultsmentioning
confidence: 95%